2018
DOI: 10.1038/s41598-018-21524-5
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of VHL Loss on Global DNA Methylome

Abstract: In clear-cell renal cell carcinoma (ccRCC), loss of von Hippel-Lindau (VHL) tumour suppressor gene and reduced oxygen tension promote stabilisation of hypoxia-inducible factor (HIF) family of transcription factors, which promote changes in the expression of genes that contribute to oncogenesis. Multiple studies have demonstrated significant perturbations in DNA methylation in ccRCC via largely unclear mechanisms that modify the transcriptional output of tumour cells. Here, we show that the methylation status o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Our finding that epigenetic dysfunction is an obligate early event is likely to be generalizable to other forms of cancer. In renal cell carcinoma, loss of the tumor suppressor von Hippel-Lindau (VHL) is widely regarded as an initiating event and associated with dramatic changes in global DNA methylation, potentially impacting subsequently acquired signaling mutations 34 . In breast cancer, mutation order is an important determinant of cancer phenotype, with luminal-type tumors demonstrating early loss of PTEN while basal-type tumors display early p53 mutation 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that epigenetic dysfunction is an obligate early event is likely to be generalizable to other forms of cancer. In renal cell carcinoma, loss of the tumor suppressor von Hippel-Lindau (VHL) is widely regarded as an initiating event and associated with dramatic changes in global DNA methylation, potentially impacting subsequently acquired signaling mutations 34 . In breast cancer, mutation order is an important determinant of cancer phenotype, with luminal-type tumors demonstrating early loss of PTEN while basal-type tumors display early p53 mutation 35 .…”
Section: Discussionmentioning
confidence: 99%
“…All values represent the mean ± SD. Asterisks indicate a significant difference (P < 0.05) binding of HIF-1α or HIF-2α and subsequently prevents the HIF-mediated transcription of HRE-containing genes [33]. Our results suggest that HRE motifs in FLT1 were methylated, suppressing the binding of HIF-α in all three choriocarcinoma cell lines, as sFLT1 production was enhanced by hypoxic stimulation after 5azadC treatment.…”
Section: Discussionmentioning
confidence: 66%
“…We recently discovered that HIF-2α, not HIF-1α, mediates the hypoxia-induced up-regulation of FLT1 expression in choriocarcinoma cell lines (BeWo, JAR, and JEG-3) and primary trophoblasts [21]. The HRE motif contains one CpG dinucleotide, and it has been confirmed that CpG methylation within this sequence prevents the binding of HIF-1α or HIF-2α and subsequently prevents the HIF-mediated transcription of HREcontaining genes [35]. Our results suggest that HRE motifs in FLT1 were methylated, suppressing the binding of HIF-α in all three choriocarcinoma cell lines, as sFLT1 production was enhanced by hypoxic stimulation after 5azadC treatment.…”
Section: Discussionmentioning
confidence: 99%